2016
DOI: 10.1016/j.diagmicrobio.2016.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent bacteremia with Streptococcus dysgalactiae: a case–control study

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 22 publications
6
18
0
Order By: Relevance
“…S . dysgalactiae of group C occasionally causes lower limb cellulitis, meningitis, and bacteremia in humans 19 21 . β-hemolytic S .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S . dysgalactiae of group C occasionally causes lower limb cellulitis, meningitis, and bacteremia in humans 19 21 . β-hemolytic S .…”
Section: Discussionmentioning
confidence: 99%
“…β-hemolytic S . dysgalactiae of groups C and G can cause severe and recurring invasive infections 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The laboratory database was reviewed to identify patients with BHS isolation from the aforementioned sterile sites. Repeated positive cultures of the same organism within 30 days of the initial isolation were considered to be from a single episode based on previous reports [15, 16] and opinions from multiple infectious disease physicians in the research team. Data on demographic characteristics, as well as laboratory, microbiological, clinical, and patients’ outcome data, were retrieved from medical records.…”
Section: Methodsmentioning
confidence: 99%
“…equisimilis (SDSE) bacteremia followed by streptococcal toxic shock syndrome in a patient with Noonan syndrome was documented in Japan [3]. Trell et al [4] performed clinical trials on patients with recurrent S. dysgalactiae bacteremia (N=22) and controls with a single episode of S. dysgalactiae bacteremia (N=92). Their case-control study showed comparable demographics, Charlson comorbidity scores, and clinical presentations.…”
mentioning
confidence: 99%
“…We retrospectively retrieved medical information of 15 patients (median age=82 years, range=64 to 88 years, 6 males and 9 females) with invasive SDSE infection because such patients possess the possibility for repetitive onsets [1234]. The information pertained to underlying medical conditions, clinical diagnoses, laboratory test data while obtaining bacterial cultures, therapeutic antimicrobial agents, surgical interventions, and outcomes.…”
mentioning
confidence: 99%